2017
DOI: 10.1007/s40195-017-0581-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Titanium and Silicon on the Swelling Behavior of 15–15Ti Steels by Heavy-Ion Beam Irradiation

Abstract: The swelling behavior of 20% cold-worked 15-15Ti steels with (0.23-0.40) wt% titanium and (0.42-0.81) wt% silicon content after heavy-ion beam irradiation has been investigated by transmission electron microscopy. The results show that 15-15Ti steel with higher titanium content displays lower swelling. As silicon content increases, the cavity size and the swelling of the 15-15Ti steels decrease obviously. Titanium and silicon may play important roles in suppressing the cavity nucleation and growth in 15-15Ti s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…To date, a number of studies on the IASCC have been reported. Studies showed that the radiation-induced microstructure is one of the key factors leading to IASCC of the steel [5][6][7][8][9][10][11][12][13][14][15]. Irradiation produces high density of defect clusters such as dislocation loops and cavities in the steels.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of studies on the IASCC have been reported. Studies showed that the radiation-induced microstructure is one of the key factors leading to IASCC of the steel [5][6][7][8][9][10][11][12][13][14][15]. Irradiation produces high density of defect clusters such as dislocation loops and cavities in the steels.…”
Section: Introductionmentioning
confidence: 99%
“…Cavity-denuded regions can be observed near regions of damage peak [18]. In order to compensate for the swelling suppression of extra interstitials, the implantation of insoluble helium before heavy-ion irradiation was frequently used to enhance cavity nucleation [11,[19][20][21]. However, the role of helium, particularly its concentration, is complicated in the evolution of swelling [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have devoted their efforts to overcoming the problems of swelling and embrittlement in austenitic steels. One of the practicable proposals is introducing precipitates within the matrix as trapping centers for He, which has been proven feasible to improve swelling and He embrittlement in materials [23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental works showed that TiC precipitates in austenitic steels is efficient for trapping He due to their finely dispersed distributions in the matrix, so that the precipitates can reduce the He accumulates at grain boundaries, and TiC precipitates is also supposed to pin the dislocation. As a result, the addition of titanium is beneficial in reducing the sensitivity of irradiation temperature to high-temperature ductility of materials [23][24][25][26][27]. It was found that the interface of phosphide particles and matrix serves as a site for the nucleation of a fine dispersion of He bubbles, and phosphorus increases the diffusivity of matrix solvent atoms, reducing the vacancy supersaturation during irradiation [28][29][30].…”
Section: Introductionmentioning
confidence: 99%